Peran Kecerdasan Spiritual Dalam Memediasi Hubungan Antara Kesiapan Teknologi Dan Kepuasan Belajar Mahasiswa Pada Era Kampus Merdeka - Ayu Tasya', Dinar; Munirul Abidin; Mudjia Rahardjo (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
This study aims to analyze the role of Spiritual Intelligence as a mediator in the relationship between Technology Readiness and Student Learning Satisfaction in the Era of Merdeka Campus. The method used was PLS-SEM analysis with data from 162 respondents. The measurement model test results showed that all indicators met the convergent validity criteria (loading > 0.7; AVE > 0.5) and reliability (Composite Reliability > 0.7). Discriminant validity was also fulfilled based on the Fornell-Larcker criterion. In the structural model test, it was found that Technology Readiness had a positive and significant effect on Learning Satisfaction (β = 0.799; p < 0.05). However, Spiritual Intelligence did not act as a mediator in this relationship, because the tested model only showed direct effects of Spiritual Intelligence on Learning Satisfaction (β = 0.758; p < 0.05) and Technology Readiness (β = 0.728; p < 0.05), with no significant indirect path. Technology Readiness and Spiritual Intelligence together were able to explain 57.5% of the variation in Learning Satisfaction (R² = 0.575). The implication of this research indicates that although Spiritual Intelligence is an important factor that directly improves Learning Satisfaction and Technology Readiness, it does not function as a mediator in this model context. Strategies to enhance learning satisfaction are suggested to focus on strengthening Technology Readiness and Spiritual Intelligence in parallel.